Therapeutic paradigm of dual targeting VEGF and PDGF for effectively treating FGF-2 off-target tumors - Kayoko Hosaka (Nature Portfolio, 2020)
Anti-VEGF therapy has many limitations that might be resolved by using combination treatment approaches. Here, the authors demonstrate that the dual-targeting of VEGF and PDGF is required for targeting resistant FGF2+ tumors which depend on the recruitment of pericytes on tumor microvessels.